Influence of Permeability and Chloride Ion Binding Capacity on Steel Corrosion in Fly Ash-Based Geopolymers - Kamei, Chikako; Hanaoka, Daishin (Journal of Asian Concrete Federation, 2026)
Geopolymers (GP) are concrete alternatives that utilize industrial by-products such as fly ash (FA) and ground granulated blast furnace slag (GGBS) as precursors, significantly reducing CO₂ emissions compared to ordinary Portland cement (OPC). However, the chloride threshold for corrosion initiation in GP remains unclear, hindering their practical adoption. Corrosion of the embedded steel was observed in GP with a chloride ion concentration of 1.0 kg/m³, but not at 0.4 kg/m³, indicating that the threshold for mixtures with 10-20% GGBs replacement was between 0.4 and 1.0 kg/m³. Comparative analysis of OPC concrete and FA-based GP revealed that differences in pore structure, pH at the reinforcement depth, and chloride binding capacity contribute to the higher susceptibility of GP to corrosion. Specifically, GP exhibited higher permeability, lower alkalinity, and negligible chloride binding compared to OPC.